Pengembangan Sistem e-Ticketing pada Dander Water Park menggunakan Digital Payment - Linda Nur Malasari; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Dander Water Park is a tourism place managed by the Department of Culture and Tourism of Bojonegoro Regency. Dander Water Park ticket counter still uses a manual system, where the ticket purchases are limited to cash payment. In addition, both visitor and ticket sales data are still reported manually. This ticket sales and reporting mechanism causing problems because tourists have to come directly to Dander Water Park to buy and find out the availability of the tickets, it also takes a long time to collect data of visitors and ticket sales, moreover, there are frequent errors found in the process of visitors data collection. This research will develop an e-ticketing system that is integrated with the Midtrans payment gateway to overcome these problems. System development was carried out using waterfall method. This research produced 21 use cases, 16 activity diagrams, 20 sequence diagrams, class diagrams consist of 11 class models and 14 class controllers, 27 UI designs, and 10 tables resulted from database design using Physical Data Model (PDM). The system implementation was carried out using MySQL with programming language PHP utilizing the Laravel 7.29.3 and Bootstrap 4.5 framework, and succeeded developing an e-ticketing system that was integrated with the Midtrans payment gateway. Black-box testing gets 100% valid results. Compatibility testing found that this system is compatible but still has several minor and major issues. User Acceptance Testing (UAT) gets final results of 78,55%, which means the system has been accepted with agreed results.